Maternal Factors and Nodal Autoregulation Orchestrate Nodal Gene Expression for Embryonic Mesendoderm Induction in the Zebrafish - Xing, Cencan; Shen, Weimin; Gong, Bo; Li, Yaqi; Yan, Lu; Meng, Anming (Frontiers in Cell and Developmental Biology, 2022)
Nodal proteins provide crucial signals for mesoderm and endoderm induction. In zebrafish embryos, the nodal genes ndr1/squint and ndr2/cyclops are implicated in mesendoderm induction. It remains elusive how ndr1 and ndr2 expression is regulated spatiotemporally. Here we investigated regulation of ndr1/ndr2 expression using Mhwa mutants that lack the maternal dorsal determinant Hwa with deficiency in -catenin signaling, Meomesa mutants that lack maternal Eomesodermin A (Eomesa), Meomesa;Mhwa double mutants, and the Nodal signaling inhibitor SB431542. We show that ndr1/ndr2 expression is completely abolished in Meomesa;Mhwa mutant embryos, indicating an essential role of maternal eomesa and hwa. Hwa-activated -catenin signaling plays a major role in activation of ndr1 expression in the dorsal blastodermal margin, while eomesa is mostly responsible for ndr1 expression in the lateroventral margin and Nodal signaling contributes to ventral expansion of the ndr1 expression domain. However, ndr2 expression mainly depends on maternal eomesa with minor or negligible contribution of maternal hwa and Nodal autoregulation. These mechanisms may help understand regulation of Nodal expression in other species.